96=14+14+(6+2(14))+(6+2(14))

Simple and best practice solution for 96=14+14+(6+2(14))+(6+2(14)) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 96=14+14+(6+2(14))+(6+2(14)) equation:


Simplifying
96 = 14 + 14 + (6 + 2(14)) + (6 + 2(14))

Multiply 2 * 14
96 = 14 + 14 + (6 + 28) + (6 + 2(14))

Combine like terms: 6 + 28 = 34
96 = 14 + 14 + (34) + (6 + 2(14))
96 = 14 + 14 + 34 + (6 + 2(14))

Multiply 2 * 14
96 = 14 + 14 + 34 + (6 + 28)

Combine like terms: 6 + 28 = 34
96 = 14 + 14 + 34 + (34)
96 = 14 + 14 + 34 + 34

Combine like terms: 14 + 14 = 28
96 = 28 + 34 + 34

Combine like terms: 28 + 34 = 62
96 = 62 + 34

Combine like terms: 62 + 34 = 96
96 = 96

Add '-96' to each side of the equation.
96 + -96 = 96 + -96

Combine like terms: 96 + -96 = 0
0 = 96 + -96

Combine like terms: 96 + -96 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 0.20x+0.25(70)=23.5 | | 96=14x | | 1/4(2x+8)=4(4-3x)+11 | | x+x+(6+2x)+(6+2x)=96 | | (n-7)(n+3)=0 | | x-45=0 | | 2x-5+2=x+2+y | | x+x+(6+x)+(6+x)=96 | | 6x=-11x+7 | | (s-3)(s-4)=0 | | 5x+9=3+8x-6 | | -7x-10=4x+23 | | 1/8(x-8)=1/16(2x+16) | | 6+4x=66 | | 10-3=1 | | 32=x+x+(2+x)+(2+x) | | 10-3=3 | | 3(k+2)=9 | | 32=(2+x)(x) | | 32=2x+x | | 18-6a=4a-(4a+3) | | 120x-42=14x+35 | | A=0.5(4+6)8 | | I=300(0.14)2 | | 135=7.5b | | -2(x-5)-3(x+4)=8 | | 13=4+b+4 | | 5q-3=9 | | 0.5(22)(38)= | | lg^2x-10x+9=0 | | 5q-1=3 | | 4x+2=48 |

Equations solver categories